Involvement of interleukin-18 in the pathogenesis of human eosinophilic esophagitis - Niranjan, Rituraj; Rajavelu, Priya; Ventateshaiah, Sathisha Upparahalli; Shukla, Jai Shankar; Zaidi, Asifa; Mariswamy, Siddesha Jalahalli; Mattner, Jochen; Fortgang, Liana; Kowalczyk, Monika; Balart, Luis; Shukla, Anshi; Mishra, Anil (Clinical Immunology, 2015)
IL-18 is induced in food allergy and EoE is food allergen-induced disease. Therefore, we tested the hypothesis whether IL-18 is involved in food allergen-induced EoE pathogenesis. Accordingly, we examined normal SPT+ and SPT- EoE patient blood and biopsy samples for IL-18, IL-18R?, ICAM and VCAM expression. Herein, we show increased IL-18 level is highly significant in food allergen SPT+ compared to SPT- EoE patients. We also report that IL-18R?+ cells and mRNA levels are induced in the esophageal biopsies of EoE patients and blood IL-18 levels correlate with esophageal eosinophilia (P<0.01). Additionally, we report that the levels of esophageal eosinophil and mast cells correlate with ICAM expression in human EoE. Mechanistically, we show that IL-18 in vitro stimulates iNKT cells and endothelial cells and induce eosinophil active cytokines IL-5 and IL-13. We provide the evidence that IL-18 is critical cytokine involved in activation of iNKT cells and ICAM in promoting human EoE.
EVALuna2:7684